2010
DOI: 10.4034/1519.0501.2010.0103.0024
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Radiation Caries in Patients Undergoing Radiation Therapy in the Head and Neck Region

Abstract: RESUMO ABSTRACTRadioterapia; Neoplasias de cabeça e pescoço; Efeitos de radiação; Cárie dentária.Radiotherapy; Head and neck neoplasms; Radiati on eff ects; Dental caries. Objecti ve: To determine the incidence of radiati on induced caries in conventi onally treated pati ents with head and neck cancer in Bosnian populati on. Method: A number of 30 pati ents with malignant diseases were included into this study, from the Clinic for Maxillofacial Surgery and Clinic for Otorhinolaryngology. All the pati ents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In Bosnian population, Konjhodzic-Prcic et al [2] reported caries incremental rate of 3.5/month for irradiated head and neck cancer patients. However, there was no caries protective regimen mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bosnian population, Konjhodzic-Prcic et al [2] reported caries incremental rate of 3.5/month for irradiated head and neck cancer patients. However, there was no caries protective regimen mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly destructive with a rapid onset, progression, and nonspecific localization. Xerostomia is the main risk factor [2]. An ideal approach to prevent radiation caries is quantitative and qualitative modification of saliva [1].…”
Section: Introductionmentioning
confidence: 99%
“…Intensity-modulated radiation therapy (IMRT) can accurately deliver radiation dose to targets while sparing adjacent normal organs with intensity modulation of high-energy photon beams so that it has favorable treatment outcomes for NPC [ 2 , 3 ]. Nevertheless, serious complications frequently occur during or after IMRT, such as xerostomia [ 4 ], radiation caries [ 5 ], dysphagia [ 6 ], taste impairment [ 7 ], and radiation-induced brain injury [ 8 ]. Thus, balancing the high-dose coverage to targets and minimum-dose exposure to organs at risk (OARs) is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma radiation therapy is still used in the treatment of patients with oral cancer (1,2) , but it might have serious negative dental and oral effects. Orofacial tissues, oral mucosa, salivary glands, taste, dentition, periodontium, bone, muscles, and joints are all affected by radiation (3) . The impact of radiotherapy on the structure of the teeth is, however, a subject of scant research.…”
Section: Introductionmentioning
confidence: 99%